Photophysical and Electro-Optical Properties of Copolymers Bearing Blue and Red Chromophores for Single-Layer White OLEDs - Despoina Tselekidou; Kyparisis Papadopoulos; Vasileios Kyriazopoulos; Konstantinos C. Andrikopoulos; Aikaterini K. Andreopoulou; Joannis K. Kallitsis; Argiris Laskarakis; Stergios Logothetidis; Maria Gioti (Nanomaterials, 2021)
In this study, novel copolymers consisting of blue and red chromophores are presented to induce emission tuning, enabling the definition of white light emission in a single polymeric layer. These aromatic polyether sulfones exhibit high molecular weights, excellent solubility and processability via solution deposition techniques. In addition, by carefully controlling the molar ratios of chromophores composition, the energy transfer mechanism, from blue to red chromophores, takes place enabling us to define properly the emission covering the entire range of the visible spectrum. The optical and photophysical properties of the monomers and copolymers were thoroughly investigated via NIR-Vis-far UV Spectroscopic Ellipsometry (SE), Absorbance and Photoluminescence (PL). These copolymers are used as an emissive layer and applied in solution-processed WOLED devices. The fabricated WOLED devices have been subsequently studied and characterized in terms of their electroluminescence properties. Finally, the WOLED devices possess high color stability and demonstrate CIE Coordinates (0.33, 0.38), which approach closely the pure white light CIE coordinates.